Barley varieties tested in 1998 and 1999: Submitted on behalf of the EBC Barley & Malt Committee - van den Berg, R. (BrewingScience, 1999)
The EBC Barley & Malt Committee organises barley variety trials in four regions in Europe: North (Denmark, Finland, Sweden and Estonia); West (Great Britain, France, Belgium, The Netherlands); Central (Germany, Hungary, Czech Republic, Slovak Republic, Austria and Slovenia); South (Portugal, Spain, Italy and Bulgaria). The spring and winter barley varieties that will be tested are selected by the Committee using transparant parameters described in the annual report; the latest issue was published in May 1998. Details of growing areas, analytical parameters of both barley and corresponding malt are made available through this report. Copies of these annual reports and more detailed information can be obtained through the national members of the Committee. The EBC Barley & Malt Committee is responsible for the organisation of the barley variety trials and for the quality of the resulting data; it is not responsible for the evaluation of the quality of the tested varieties. Rating of the barley varieties tested in the four regions is the responsibility of each individual company or institute.